Account Blocking Without Customer Consent: Disharmony Between The Banking Law, The PDP Law, and POJK 8/2023 - Yulius Ariyasatya; Luthy Yustika (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Banks blocking customer accounts without consent or notification raises legal issues related to customer protection and data privacy. Under the framework of Law No. 7/1992 in conjunction with Law No. 10/1998, such actions can be justified as an exception if based on orders from law enforcement officials. However, following the enactment of POJK No. 22/2023 concerning Consumer Protection in the Financial Services Sector and Law No. 27/2022 concerning Personal Data Protection, the practice of blocking accounts without customer consent has the potential to conflict with the principles of transparency, accountability, and control of personal data by banks. This study normatively analyzes the potential for disharmony between regulations through a review of laws and regulations, legal literature, and banking practices, using the Theory of Legal Protection and the Theory of Presumption of Innocence as analytical tools. The study's findings demonstrate the need for adequate consent and notification in any action that impacts customer rights, as well as strengthening operational harmonization and oversight so that blocking procedures do not violate privacy rights or legal certainty. Recommendations include the development of clear operational standards, transparency of processes, and accountability of banks as data controllers, so that customer legal protection is optimally achieved.